Potential Reduction of Low-Density Polyethylene (LDPE) Plastic Waste as A Paving Block Mixed Material - Aryasatiani, John Acrimus; Alfiah, Taty (Journal of Civil Engineering, Planning and Design, 2022)
Paving blocks are the result of a mixture of Portland cement, sand, water, and with or without other additives. Based on the results of sampling the composition of plastic waste in temporary shelters for 7 days, the percentage of plastic waste generated is 14%, whereas the percentage of LDPE plastic waste is 8% and the non-LDPE is 6%. This research was conducted with a ratio of cement and sand of 1: 4 with variations of a mixture of low-density polyethylene (LDPE) plastic at 0%, 0.5%, 1%, 1.5%, and 2% by weight of sand. Paving block quality testing was carried out at the Environmental Engineering and Quality Laboratory, Department of Environmental Engineering and Concrete Laboratory, Civil Engineering, Adhi Tama Institute of Technology Surabaya. The results of the study showed that the greatest compressive strength was obtained in paving blocks with a plastic variation of 0.5%, which is 24,83 MPa. While the lowest compressive strength value is obtained at the paving block variation of 1.5%, which is 12.32 Mpa. The test results for the largest water absorption were obtained on paving blocks with a plastic variation of 2% with an average absorption of 6.45%, while the lowest water absorption was found in paving blocks with 1% plastic variation with an average absorption of 4.65%. it was concluded that the addition of reduced density polyethylene (LDPE) plastic from 0.5% to 2% had no significant impact on the addition of compressive strength and water absorption but tended to experience a decrease in the quality of the comparison sample. The potential for reducing LDPE plastic waste is 203,376 grams/day and produces 8,135 paving blocks with quality B. The purpose of this study is to the utilization of low-density polyethylene (LDPE) plastic waste in paving blocks and the effect on the quality of compressive strength and water absorption.